Genetic diversity of Rhizophora mucronata on the western coast of Timor Island - Ihwan Ihwan; Rusydi Rusydi; Uslan Uslan; Nashi Widodo; Luchman Hakim (Kuwait Journal of Science)
The mangroveRhizophoramucronatathat grows on the western coast of Timor Island is undertreated by various anthropogenic activities, such as logging for firewood and other household needs, which require a strategy for sustainable development. Information on the genetic diversity of the species is important to plan for coastal management and conservation of the mangrove.  Therefore, we conducted a study on mangrove genetic diversityon the western coast of Timor Island. Mangrove leaf samples were collected from 10 locations. Samples underwent DNA isolation and random amplified polymorphic DNA testing using six primers. The R. mucronatapopulation formed three main groups and 12 subgroups with a similarity coefficient value of 0.42, and the genetic proximity among populations is not related to geographical distance. Further analysis suggested that the genetic diversity of R. mucronataon Timor Island can be classified as moderate. The highest degree of genetic diversity was found in Sumlili (Ne = 2.999, Na = 11.167, He = 0.667), whereas the lowest genetic diversity was found in Sulamu (Ne = 2.967, Na = 11.833, He = 0.663). The environmental stress and dry climate condition might be a factor in the genetic diversity of the mangrove at the moderate level.